2021
DOI: 10.1128/jvi.02167-20
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Type 1 Interferon Responses Are Critical for Control of Systemic Reovirus Dissemination

Abstract: Mammalian orthoreovirus (reovirus) spreads from the site of infection to every organ system in the body via the blood. However, mechanisms that underlie reovirus hematogenous spread remain undefined. Non-structural protein σ1s is a critical determinant of reovirus bloodstream dissemination that is required for efficient viral replication in many types of cultured cells. Here, we used the specificity of the σ1s protein for promoting hematogenous spread as a platform to uncover a role for lymphatic type-1 interf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 63 publications
(92 reference statements)
4
5
0
Order By: Relevance
“…Similar mechanisms have been proposed in encephalitic flavivirus infection, where IFN-λ reduces blood-brain barrier permeability and viral transport (Lazear et al, 2015). These data also add to recent findings that viruses may specifically subvert the lymphatic vasculature to disseminate via lymph (Phillips et al, 2021), together indicating that the lymphatic vasculature is a critical innate barrier to viral dissemination from peripheral tissue.…”
Section: Dermal Zippering Reduces Fluid Transport and Restricts Viral...supporting
confidence: 79%
“…Similar mechanisms have been proposed in encephalitic flavivirus infection, where IFN-λ reduces blood-brain barrier permeability and viral transport (Lazear et al, 2015). These data also add to recent findings that viruses may specifically subvert the lymphatic vasculature to disseminate via lymph (Phillips et al, 2021), together indicating that the lymphatic vasculature is a critical innate barrier to viral dissemination from peripheral tissue.…”
Section: Dermal Zippering Reduces Fluid Transport and Restricts Viral...supporting
confidence: 79%
“…We also assessed virulence following intracranial (IC) inoculation. Similar to oral inoculation, T1 reoviruses also disseminate systemically following IC inoculation (28,29). Like we observed following oral inoculation, T1L/T3DM2 produced higher viral titers at earlier time points and had higher peak viral loads compared to T1L in each organ when virus was introduced IC ( .…”
Section: T1l/t3dm2 Replicates and Disseminates More Efficiently Than T1l In Vivosupporting
confidence: 65%
“…We previously also demonstrated that host type I IFN sensing was required for reduced fluid transport and viral sequestration following VACV scarification (Loo et al, 2017), however, whether type I IFNs act through lymphatic-specific changes in junctional morphology remains to be explored. These data add to recent findings that viruses may also specifically acquire mechanisms to subvert the lymphatic vasculature to mediate dissemination from the site of infection (Phillips et al, 2020). The nonstructural protein s1s expressed by orthoreovirus suppresses type I IFN responses in LECs and may result in direct release of viable virions into lymph driving dissemination.…”
Section: Dermal Zippering Reduces Fluid Transport and Restricts Viral Dissemination To Lymph Nodessupporting
confidence: 64%
“…The nonstructural protein s1s expressed by orthoreovirus suppresses type I IFN responses in LECs and may result in direct release of viable virions into lymph driving dissemination. In the absence of s1s, LEC-derived type I IFN responses limit orthoreovirus dissemination from the intestine (Phillips et al, 2020). Together this work indicates that the lymphatic vasculature is a critical barrier to viral dissemination from peripheral non-lymphoid tissue.…”
Section: Dermal Zippering Reduces Fluid Transport and Restricts Viral Dissemination To Lymph Nodesmentioning
confidence: 70%